The Process of Innovation Diffusion and Adoption of Innovations in the Implementation of Community-Based Total Sanitation Policy in South Sumatera - IMANIA, Katriza; SUWITRI, Sri; WARELLA, Yoppie; SENIH, Nurmah (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.11.1(41).10, 2020)
The Ministry of Health of the Republic of Indonesia established policy number 13 of 2014 concerning Community-Based Total Sanitation (STBM) which aims to change people's behaviour in hygienic behaviour in sanitation development. Changes in community behaviour are very important, because of the increased vulnerability of people affected by diarrheal diseases, especially in the Pemulutan region, Ogan Ilir Regency, South Sumatra Province. The STBM policy can be achieved through policy diffusion which is influenced by factors of innovation and adoption by the community. The study tried to describe the implementation of STBM policies. The study used a qualitative approach, supported by primary and secondary data obtained through in-depth interviews and observation techniques. The results showed that the process of innovation and adoption of the STBM implementation policy in the Pemulutan region had not yet run optimally, although the community realized that the policy was very beneficial to improve the quality of life of sanitation environment. Various obstacles still occur including the content and policy context factors that are understood by the community, integrated service post ( posyandu ) cadres, and midwives as technical implementers in implementing policies.